The Effect Of European Union's Implementation Of The Russian Economic Embargo On International Trade Sector - Yogi Muhammad Rahman; Widya Jusu Adeningtyas; Belardo Prasetya Mega Jaya (Faculty of Law, Universitas Jenderal Soedirman, 2023)
This study analyzes effect of European Union's implementation economic embargo on Russia after Russian invasion of Ukraine. Embargoes imposed was stoppage imports of petroleum and natural gas from Russia. This situation impact of circulation oil and natural gas prices on global market because Russia is the world's largest supplier oil and natural gas. The purpose study is to analyze effect of implementation Russian embargo on international trade sector and examine impact implementation embargo sanctions on Russian economy. The research methodology used is normative juridical. The results show that implementation of embargo against Russia will trigger escalation the price of crude oil and natural gas which are becoming scarce on the global market and significantly reduce availability of grain, wheat, barley and corn commodities while for Russia this case cause increase inflation due to Russia lost most of its shares in international markets.